2013
DOI: 10.1128/aem.03768-12
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Inactivation of Mycobacterium avium subsp. paratuberculosis during Composting of Livestock Carcasses

Abstract: f Mycobacterium avium subsp. paratuberculosis causes Johne's disease (JD) in ruminants, with substantial economic impacts on the cattle industry. Johne's disease is known for its long latency period, and difficulties in diagnosis are due to insensitivities of current detection methods. Eradication is challenging as M. avium subsp. paratuberculosis can survive for extended periods within the environment, resulting in new infections in naïve animals (W. Xu et al., J. Environ. Qual. 38:437-450, 2009). This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Coloured lines indicate samples which achieved different temperature profiles (black lines: <55°C and; red lines: >55°C) previously reported by Tkachuk et al . (). Significance of sample clustering between each temperature group determined with unweighted U ni F rac ( P < 0·01).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Coloured lines indicate samples which achieved different temperature profiles (black lines: <55°C and; red lines: >55°C) previously reported by Tkachuk et al . (). Significance of sample clustering between each temperature group determined with unweighted U ni F rac ( P < 0·01).…”
Section: Resultsmentioning
confidence: 97%
“…() and reprinted from Tkachuk et al . () with permission from the A merican S ociety of A gronomy ( ASA ), the C rop S cience S ociety of A merica ( CSSA ) and the S oil S cience S ociety of A merica ( SSSA ).…”
Section: Methodsmentioning
confidence: 99%
“…Mycobacterium paratuberculosis has been shown to survive in a variety of environmental conditions ranging from several weeks in barn dust samples to almost two years in river sediment (Pickup et al, 2005;Tkachuk et al, 2013). This highlights the plausible link between ruminant excretion of M.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies showed composting was ineffective at eliminating M. paratuberculosis (Tkachuk et al, 2013) and M. paratuberculosis can survive in a biogas plant for up to 6 months with DNA detectable by PCR for longer . In experimental challenge trials invertebrates were shown to be competent M. paratuberculosis hosts; protozoa (Whan et al, 2006) and nematodes (Lloyd et al, 2001) were shown to take up the organism and provide a host environment for M. paratuberculosis to survive and replicate; another study demonstrated persistence and replication within protists over 24 weeks (Mura et al, 2006).…”
Section: Prevalence In the Environmentmentioning
confidence: 99%
“…Furthermore, while the detection of viable MAP is greatly reduced in thermophilic compost compared to liquid manure, MAP DNA can be detected in compost up to 56 days and liquid manure up to 175 days [75]. Composting has also been shown to be ineffective for decontamination of carcasses infected with MAP, even after 250 days [76]. This indicates that proper thermophilic composting could reduce the danger of recycling MAP on the farm, but only if contaminated carcasses are disposed otherwise.…”
Section: Crop Managementmentioning
confidence: 89%